Bio-based polyurethane as a sustainable coating material for controlled-release fertilizer - Lyu Yao; Azizah Baharum; Lih Jiun Yu; Zibo Yan; Khairiah Haji Badri (Discover Sustainability)
Abstract Polyurethane (PU) offers broad applications due to its excellent performance and diverse formulation design. In agriculture, PU coatings have been used to regulate nutrient release by using controlled release fertilizer (CRF). This gradual release ensures that plants receive sufficient nutrients throughout the growing cycle, improving the utilization rate of nutrients and reducing environmental pollution. Traditional petroleum-based PU coating in the production of CRF has been gradually replaced by bio-based PU due to its high cost and associated environmental risk. In this study, a bio-based PU coating synthesized from palm kernel oil-based polyol and methylene diphenyl diisocyanate (MDI) was coated onto urea granules using a micro scale coating machine. Two key parameters were studied, which are the NCO/OH ratio (0.8:1, 1:1, 1.2:1) and coating amount (4%, 9%, 14%). The bio-based PU coated urea could release nutrients by absorbing moisture from the air. The CRF with 9% coating amount and NCO/OH ratio of 1:1 reached 56 days release period. Pot experiments using mung beans indicated improved agronomic efficacy. The CRF with 4% coating and NCO/OH ratio at 1:1, resulted in 400% increase in dry weight compared to uncoated urea. Toxicity test showed that the bio-based PU microplastic had no adverse effect on the growth of mung beans. These findings suggest that palm kernel oil-based PU-coated fertilizers are a promising solution for sustainable agricultural practices.